THE LOWER PALEOLITHIC INDUSTRY OF ANKHE IN VIETNAM WITH THE SO-CALLED MOVIUS LINE - Nguyễn Khắc Sử (Tạp chí Khoa học Đại học Đà Lạt)
From 2014 to 2019, four of 23 Lower Paleolithic sites were excavated by a joint Vietnamese - Russian team of archaeologists in Ankhe town, Gialai province. The An Khe industry is characterized by a collection of stone tools made of local river and stream quartz, quartzite pebbles which are large, hard, and fine grained. Typologically, the representative tools are a complex of bifacial tools/handaxes, picks/triangular-sectioned picks, and choppers/chopping tools. The An Khe industry is dated by the K-Ar isotope method resulting in dates of 806,000 ± 22,000BP and 782,000 ± 20,000BP. The An Khe industry has similar characteristics in terms of material, technique, type, and date to the Baisei (China) industry. The archaeological discoveries in Vietnam and China show that bifaces appear from the Early Paleolithic. It would be a serious mistake to argue that those who manufactured handaxes represented a dynamic and advanced area, while the others who produced choppers/chopping tools represented a conservative and backward one.